Factors associated with IADL independence: implications for OT practice. (4th March 2017) - Chen, Szu-Wei; Chippendale, Tracy
Abstract: Background: Globally, the population is aging. Instrumental activities of daily living (IADL) are an important component of independent function and impact the ability of older adults to age in place. Therefore, factors associated with IADL independence warrant further study. Objective: To explore the association of age, depressive symptoms and leisure participation with IADL independence, and the relative importance of these three factors in predicting IADL independence. Methods: A cross-sectional design using an existing data set was employed. Older adults age 60 and older ( n = 98) who resided in senior housing or their own home/apartment were included in the study. A hierarchical multiple regression analysis was employed. Results: The second model predicting IADL independence using age, depressive symptoms and level of leisure participation was significant ( F (3, 96) = 15.57, p < 0.001) and explained 31.00% of the variance in IADL independence compared to the first regression model, which included age alone ( R 2 adjusted = 18.00%). Age was the strongest of the three predictors, accounting for 11.40% of the variance in IADL independence. Depressive symptoms and participation in leisure activities were also significant predictors, their unique contributions being 7.30 and 4.30%, respectively. Conclusion and significance: Age, depressive symptoms and leisure participation are all significant predictors of IADL independence among older adults. Therefore, according to our preliminary findings, leisure participation and non-pharmacological interventions for depressive symptoms warrant attention in practice in relation to IADL independence.